Keabsahan Surat Keputusan Gubernur Jawa Tengah Pasca Putusan Mahkamah Agung Tentang Penambangan Pabrik Semen - Albar, Zainuddin Amriti (Jurnal Cakrawala Hukum, 2019)
This study aims to examine the validity of the Central Java Governor Decree Number 660.1 / 6 of 2017 concerning permits for the construction and mining of cement factories after the cancellation of the previous Governorâ€™s Decree by the Supreme Court Number 99 PK / TUN / 2016. The Supreme Court overturned the construction and mining of cement factories because they had a negative impact on the environment. Mining of cement plants in the Rembang area is declared not in accordance with the environmental impact analysis because in the mining area of the cement plant there is a Groundwater Basin whose preservation is protected by law. This research includes the type of normative research. The research that has been carried out has been obtained that substantially the Central Java Governor Decree Number 660.1 / 6 of 2017 was declared invalid even though on the grounds that there was an improvement in the EIA because of the Supreme Courtâ€™s decision as the highest court that every decision could not be contested. However, the suggestion should be that the contents of the Supreme Courtâ€™s ruling did not lead to the perception that the development was continued by changing the EIA. How to cite item:Â Albar, Z. (2019). Keabsahan Surat Keputusan Gubernur Jawa Tengah Pasca Putusan Mahkamah Agung Tentang Penambangan Pabrik Semen.Â Jurnal Cakrawala Hukum, 10(1), 107-117. doi:https://doi.org/10.26905/idjch.v10i1.3117